2007
DOI: 10.1080/10413200701599173
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Types of Confidence Identified by World Class Sport Performers

Abstract: This study identified the sources and types of confidence salient to 14 (7 male, 7 female) successful World Class athletes. Nine sources of confidence were identified: Preparation, performance accomplishments, coaching, innate factors, social support, experience, competitive advantage, self-awareness, and trust. A testament to the multi-dimensional nature of sport confidence, six types of sport confidence were also identified: skill execution, achievement, physical factors, psychological factors, superiority t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
134
5
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(163 citation statements)
references
References 29 publications
18
134
5
6
Order By: Relevance
“…Although the preceding discourse has provided tentative alliances between the use of advanced psychological strategies and certain dimensions of the anxiety response, it is difficult to reach any definitive conclusions from the existing evidence for three reasons: (a) examining advanced psychological strategies was not the central aim of the studies reported (e.g., Connaughton et al, 2008), (b) no inference was made to competitive anxiety (e.g., Hays et al, 2007), and/or (c) the intervening mechanisms that underlie the purported effects were not disclosed (e.g., Lonsdale & Tam, 2008). Consistent with recommendations for future research (e.g., Fletcher & Hanton, 2001;, these observations highlight the value in providing a more detailed insight into these relationships to inform coaches and consultants working with athletes debilitated by competitive anxiety.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Although the preceding discourse has provided tentative alliances between the use of advanced psychological strategies and certain dimensions of the anxiety response, it is difficult to reach any definitive conclusions from the existing evidence for three reasons: (a) examining advanced psychological strategies was not the central aim of the studies reported (e.g., Connaughton et al, 2008), (b) no inference was made to competitive anxiety (e.g., Hays et al, 2007), and/or (c) the intervening mechanisms that underlie the purported effects were not disclosed (e.g., Lonsdale & Tam, 2008). Consistent with recommendations for future research (e.g., Fletcher & Hanton, 2001;, these observations highlight the value in providing a more detailed insight into these relationships to inform coaches and consultants working with athletes debilitated by competitive anxiety.…”
mentioning
confidence: 95%
“…The last advanced psychological strategy, Overlearning of Skills, is where athletes repeatedly execute the physical and mental skills that they are going to reproduce in competition (Hardy et al, 1996). Associated literature has identified this strategy to have important psychological benefits for competitive athletes (e.g., Connaughton, Wadey, Hanton, & Jones, 2008;Hays et al, 2007). For instance, Hays et al (2007) reported that overlearning of skills was a salient source of self-confidence in world-class sporting performers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hays and colleagues (Hays, Maynard, Thomas, & Bawden, 2007) were the first to investigate sport confidence in successful world-class sports performers. They identified sources and types of confidence used by athletes competing on the world stage and demonstrated that demographic and organizational factors influence the development of confidence in such athletes.…”
Section: Introductionmentioning
confidence: 99%